Effectiveness of blood flow restricted exercise compared with standard exercise in patients with recurrent low back pain: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Amano, Shinichi; Ludin, Arimi; Clift, Rachel; Nakazawa, Masato; Law, Timothy; Rush, Laura; Manini, Todd; Thomas, James; Russ, David; Clark, Brian
Abstract Background Low back pain is a highly prevalent condition in the United States and has a staggeringly negative impact on society in terms of expenses and disability. It has previously been suggested that rehabilitation strategies for persons with recurrent low back pain should be directed to the medial back muscles as these muscles provide functional support of the lumbar region. However, many individuals with low back pain cannot safely and effectively induce trunk muscle adaptation using traditional high-load resistance exercise, and no viable low-load protocols to induce trunk extensor muscle adaptation exist. Herein, we present the study protocol for a randomized controlled trial that will investigate the "cross-transfer" of effects of a novel exercise modality, blood flow restricted exercise, on cross-sectional area (primary outcome), strength and endurance (secondary outcomes) of trunk extensor muscles, as well as the pain, disability, and rate of recurrence of low back pain (tertiary outcomes). Methods and study design This is a single-blinded, single-site, randomized controlled trial. A minimum of 32 (and up to 40) subjects aged 18 to 50 years with recurrent low back pain and poor trunk extensor muscle endurance will be recruited, enrolled and randomized. After completion of baseline assessments, participants will be randomized in a 1:1 ratio to receive a 10-week resistance exercise training program with blood flow restriction (BFR exercise group) or without blood flow restriction (control exercise group). Repeat assessments will be taken immediately post intervention and at 12 weeks after the completion of the exercise program. Furthermore, once every 4 weeks during a 36-week follow-up period, participants will be asked to rate their perceived disability and back pain over the past 14 days. Discussion This study will examine the potential for blood flow restricted exercise applied to appendicular muscles to result in a "cross-transfer" of therapeutic effect to the lumbar musculature in individuals with low back pain. The results of this study will provide important insights into the effectiveness of this novel exercise modality, which could potentially provide the foundation for a cost-effective and easy-to-implement rehabilitation strategy to induce muscle adaptation in the absence of high mechanical and compressive loading on the spine. Trial registration This trial is registered with ClinicalTrials.gov (registration number:NCT02308189, date of registration: 2 December 2014).